2007
DOI: 10.1111/j.1365-2222.2007.02831.x
|View full text |Cite
|
Sign up to set email alerts
|

Atopy and new‐onset asthma in young Danish farmers and CD14, TLR2, and TLR4 genetic polymorphisms: a nested case‐control study

Abstract: The CD14/-260 and CD14/-651 promoter polymorphisms are associated with atopy prevalence among young adults exposed to farm environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
3
5

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 44 publications
3
66
3
5
Order By: Relevance
“…Although Eder et al 24 detected an association between a promoter SNP in TLR2 and asthma in children of European farmers, they found no association between asthma and rs3804100. Also, Smit et al 25 did not find any associations between TLR2 SNPs and asthma in a population of Danish farmers, but they did not include the polymorphisms analyzed in the present study.…”
Section: Tlr2mentioning
confidence: 62%
See 1 more Smart Citation
“…Although Eder et al 24 detected an association between a promoter SNP in TLR2 and asthma in children of European farmers, they found no association between asthma and rs3804100. Also, Smit et al 25 did not find any associations between TLR2 SNPs and asthma in a population of Danish farmers, but they did not include the polymorphisms analyzed in the present study.…”
Section: Tlr2mentioning
confidence: 62%
“…[13][14][15] Likewise, asthma has in some studies been associated with polymorphisms in TLR2, 16 TLR4 17 and CD14, 18 but not in others. [19][20][21] Epidemiological studies suggest a negative relation between asthma and T1D 22 and certain genes appear to have associations in opposite directions for these two diseases. 23 To our knowledge, polymorphisms in these PRRs have not been compared in relation to T1D and allergic asthma, and the recent observation that PRRs are involved in regulation of Th1 versus Th2 responses raises the question of common genetic variants in these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies in adult farmers and young adults with a farming background showed that the CD14/-260T (also reported in the literature as CD14/-159T ) allele was inversely associated with atopy [65,66], whereas the CD14/-651T allele was positively associated with atopy [66]. The associations were strongest in those farmers who were born on the farm or lived on a farm for the first year of life [65,66], suggesting an interaction with timing of exposure. In farmers' children, a bimodal effect of CD14/-260 on atopy was shown, with the direction of the effect being dependent on the type and level of environmental exposures (i.e., pets, livestock and endotoxin) [64].…”
Section: Immunological Mechanismsmentioning
confidence: 94%
“…A subsequent study in farmers' children showed a significant dose-response association between maternal exposure to farm animals and gene expression of TLR2, TLR4 and CD14 [47]. Two studies in adult farmers and young adults with a farming background showed that the CD14/-260T (also reported in the literature as CD14/-159T ) allele was inversely associated with atopy [65,66], whereas the CD14/-651T allele was positively associated with atopy [66]. The associations were strongest in those farmers who were born on the farm or lived on a farm for the first year of life [65,66], suggesting an interaction with timing of exposure.…”
Section: Immunological Mechanismsmentioning
confidence: 99%
“…Αρχικά σε µελέτη 589 οικογενειών της νότιας Αµερικής και 167 οικογενειών του Κεµπέκ δεν διαπιστώθηκε συσχέτισή τους µε την εκδήλωση ασθµατικού φαινότυπου [245], και το αποτέ-λεσµα επαναλήφθηκε σε νεαρούς ∆ανούς αγρότες [246]. Μελέτη σε γερµανικό πληθυσµό, κατέληξε στο συµπέρασµα ότι οι συµµετέχοντες µε wt γονότυπο είχαν αυξηµένο κίνδυνο ά-σθµατος µε εντονότερη έκθεση στην ενδοτοξίνη, σε αντίθεση µε τους φέροντες τους δύο πο- συσχετίστηκε µε την παρουσία του πολυµορφισµού Asp299Gly σε µελέτη οικογενειών µε α-σθµατικά µέλη, αλλά και πάλι δεν διαπιστώθηκε συσχέτιση µε τον κίνδυνο εκδήλωσης ά-σθµατος [248].…”
Section: μελέτη συσχέτισηunclassified